The Study on the Implementation of Barangay Ordinance during COVID-19 Pandemic in Barangay Commonwealth Quezon City: Vol. 3, No. 1A (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In 2019, the world was shocked by the emergence and increase of cases of people affected by a new virus called COVID-19. The effects of COVID-19 have many changes in people's daily lives. The Quezon City government apprehended 819 individuals in a joint operation conducted by the Department of Public Order and Safety, QC Police District, Task Force on Transport and Traffic Management, and Task Force Disiplina on the first day of the imposition of curfew hours from 10 pm to 5 am in Metro Manila. The violators were brought to their respective barangays and were issued an Ordinance Violation Receipt (OVR). Apprehended individuals must pay the fine before it lapses in five days. Failure to do so would result in filing charges before the City Prosecutor's Office, which will reflect on the violator's police clearance upon application. Implementing public safety hours and wearing facemasks in public places impose a fine of P300, P500, or P1,000 for the first, second, and third offences. The penalties for violating public safety hours include one (1) month imprisonment and a fine of P1,000 for the third offence.The researchers used the descriptive method mixed with a phenomenological approach. The researchers interviewed the barangay personnel and residents. The barangay personnel and residents highly agree with wearing complete and proper uniforms during duties. Wearing a complete and proper uniform during duties is strongly agreed upon. As attested by the respondents, the recommendations proposed by the researchers, installing CCTV cameras in every street for 24-hour monitoring surveillance, were rated as highly recommended. The study's findings on implementing barangay ordinance during the COVID-19 pandemic are that many residents followed the ordinance for their health and safety to decrease COVID-19 cases. They made way for it not to multiply the infected in their barangay. The barangay personnel or the front-liners in Barangay Commonwealth are doing well in their job and giving better tight security. Sometimes, the protocol in the market is not followed, and there are always hardheaded people. Hence, the barangay personnel find a way to protect the health and safety of people in their communities.